(untitled) (Harmoni, 2022)
A Wahhabi leader’s controversial lecture on a grave pilgrimage on the island of Lombok has become the seed of religious conflict and has become a national issue. This paper explores how the pattern of da’wah (delivery of lectures), the response of the community, and its impact on the building of religious harmony. Through a content analysis approach and social response, the paper concludes that first, the da’wah pattern uses a textual approach to the arguments of the Qur’an and Hadith where the topic of discussion is still about ikhtilaf matters that have been around for quite a long time such as the law of tomb pilgrimage, tahlilan, and maulidan. Second, the response of the Lombok Muslim community to the Wahhabi lecture on the Law of religious tourism for pilgrimage pilgrimages was negative, which was marked by the emergence of demonstrations and reporting of the preacher to the police. This response is not only a response to lectures about tomb pilgrimages, but is a response to the da’wah pattern that has been used by the Wahhabi. Third, the lecture on the tomb pilgrimage which received a negative response has become a threat to the building of religious harmony on the island of Lombok. This fact occurs because the understanding of tomb pilgrimage that ’should not’ clash with religious traditions which actually ’recommend’. The social conflict that immediately ignited when the lecture went viral became a clear indicator that the Wahhabi da’wah pattern had become a threat to religious disharmony on the island of Lombok. A dialogue of religious understanding is needed to stem the threat of disharmony in order to maintain a harmonious social life. It can be reflected from the three findings that the process of religious da’wah must take into account the historical background and understanding of the target community of da’wah. Issues of ikhtilaf in religious theology should not need to be present in the pulpit of da’wah which is public and open (online). It is hoped that the Wahhabis and Aswaja groups will respect each other and prevent statements that can trigger religious conflicts.